Spatial-temporal analysis of leprosy in a priority Brazilian northeast municipality for disease control - Fernanda de Castro Lopes; Giana Gislanne da Silva de Sousa; Weslei Melo da Silva; Ana Cristina Pereira de Jesus Costa; Floriacy Stabnow Santos; Lívia Maia Pascoal; Marcelino Santos Neto
ABSTRACT Objectives: to analyze the spatial-temporal distribution of leprosy in a priority municipality for leprosy control. Methods: ecological study, conducted in a city in the Northeast of Brazil, whose analysis units were census sectors. The study used compulsory notification data for cases registered between 2008 and 2017. TerraView software and the Batch Geocode tool was used for geocoding. The detection of spatial-temporal agglomerations of high relative risks was done by scanning statistics. Results: the spatial-temporal distribution of cases was heterogeneous, creating four agglomerations of high relative risks in the urban area of the municipality between the years 2008 and 2012; and annual prevalence rates classified from high to hyperendemic. Conclusions: areas of higher risk and concentration of the disease in space-time were linked to the characteristics of high population density and social vulnerability of these spaces, raising the prioritization of health professionals' actions, systems, and services for control, and monitoring the disease.